Candidate gene expression patterns in rabbit preimplantation embryos developed in vivo and in vitro - Henderson, Gibence Rose Winnie (Springer US, 2014)
PURPOSE: The levels and timing of expression of genes like BCLXL, HDAC1 and pluripotency marker genes namely, OCT4, SOX2, NANOG and KLF4 are known to influence preimplantation embryo development. Despite this information, precise understanding of their influence during preimplantation embryo development is lacking. The present study attempts to compare the expression of these genes in the in vivo and in vitro developed preimplantation embryos. METHODS: The in vivo and in vitro developed rabbit embryos collected at distinct developmental stages namely, pronuclear, 2 cell, 4 cell, 8 cell, 16 cell, Morula and blastocyst were compared at the transcriptional and translational levels using Real Time PCR and immunocytochemical studies respectively. RESULTS: The study establishes the altered levels of candidate genes at the transcriptional level and translational level with reference to the zygotic genome activation (ZGA) phase of embryo development in the in vivo and in vitro developed embryos. The expression of OCT4, KLF4, NANOG and SOX2 genes were higher in the in vitro developed embryos whereas and HDAC1 was lower. BCLXL expression had its peak at ZGA in in vivo developed embryos. Protein expression of all the candidate genes was observed in the embryos. BCLXL, KLF4 and NANOG exhibited diffused localisation whereas HDAC1, OCT4, and SOX2 exhibited nuclear localisation. CONCLUSIONS: This study leads to conclude that BCLXL peak expression at the ZGA phase may be a requirement for embryo development. Further expression of all the candidate genes was influenced by ZGA phase of development at the transcript level, but not at the protein level.